Warehouse Management Information System On Maklon Services With Economic Order Quantity Method - Arfin, Ardinal; Sifaunajah, Agus (NEWTON: Networking and Information Technology, 2025)
CV. XYZ is a maklon services provider that partners with other businesses to manufacture snacks. Currently, incoming and outgoing goods data is still managed manually and there is no technology-based warehouse management information system. This study aims to design a website-based warehouse management information system that can be used to manage goods in the warehouse. The system in this study was designed using the waterfall method. This warehouse management information system is website-based and created using the CodeIgniter 3 framework with PHP and MySQL programming languages as its database and its editor tools using Visual Studio Code. The result of this research is the creation of a warehouse management information system that can manage goods in the warehouse so that it can facilitate the work of managing incoming goods, outgoing goods, and stock of goods in the warehouse. With the existence of a website-based warehouse management information system, the system used can be changed to a computerized system, so that it is expected to help in managing goods in the warehouse to be more effective and efficient, as well as the presentation of stock reports to be more accurate and the information can be used to help in the decision-making process to accelerate the company's performance, especially in warehousing.